2022
DOI: 10.4209/aaqr.220015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Source Appointment and Health Risk of PM2.5 and PM2.5-10 during Forest and Peatland Fires in Riau, Indonesia

Abstract: This study investigated the contributions of particulate matter (PM) from various emission sources during the dry season, which resulted from frequent fires occurring in degraded forests and peatlands in Indonesia. Samples of fine (PM2.5) and coarse (PM2.5-10) particles collected during the dry season in Riau, Indonesia were analyzed to determine the mass concentrations of metallic trace elements, ionic compound, black carbon (BC), and organic carbon (OC). The average concentrations of PM2.5 and PM2.5-10 at Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The advantage of using PMF analyses is that they can handle incomplete data, such as data with negative values, missing data and data below the limit of detection. However, there were no negative values, missing data or data below the limit of detection in this study (Chueinta et al, 2000, Siregar et al, 2022 ). Adeyemi et al ( 2021 ) performed similar analyses and found that the best results were obtained using the lowest Q value.…”
Section: Methodsmentioning
confidence: 55%
“…The advantage of using PMF analyses is that they can handle incomplete data, such as data with negative values, missing data and data below the limit of detection. However, there were no negative values, missing data or data below the limit of detection in this study (Chueinta et al, 2000, Siregar et al, 2022 ). Adeyemi et al ( 2021 ) performed similar analyses and found that the best results were obtained using the lowest Q value.…”
Section: Methodsmentioning
confidence: 55%
“…Relevant medical and epidemiological researches report that long-term exposure to PM2.5 can cause respiratory, cardiovascular, and even carcinogenic diseases. Medical evidence also show that PM2.5 concentration is positively correlated with the inpatient and mortality rates in the heavily polluted metropolitan areas (Siregar et al, 2022;Wang et al, 2022). Both acute and chronic diseases caused by long-term PM2.5 exposure include asthma, cough, pneumonia, bronchitis, and high blood pressure (Sánchez-Piñero et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, biomass combustion remains a significant source of indoor air pollution since most households using biomass fuels often cook indoors, using open fires in poorly ventilated houses (Bruce et al 2000, Balmes 2019). In general, incomplete combustion of biomass fuels leads to the generation of particulate matter (PM) with aerodynamic diameters ≤ 10 µm (PM 10 ) and 2.5 µm (PM 2.5 ), carbon monoxide (CO) and aerosols that may contain carcinogenic and mutagenic toxins, such as polycyclic aromatic hydrocarbons (PAHs) (e.g., benzo[a]pyrene (BaP)) (Bruce et al 2000, Kim et al 2012, Du et al 2020, Yu et al 2020, Siregar et al 2022.…”
Section: Introductionmentioning
confidence: 99%